Factors associated with patient-reported experiences and outcomes of substance use disorder treatment in Cape Town, South Africa - Myers-Franchi, Bronwyn; Koch, J.R.; Johnson, K.; Harker, N. (BMC, 2022)
Background: Interventions are needed to improve the quality of South Africa’s substance use disorder (SUD) treatment system. This study aimed to identify factors associated with patient-reported suboptimal access, quality, and outcomes of SUD treatment to guide the design of targeted quality improvement initiatives. Method: We analysed clinical record and patient survey data routinely collected by SUD services in the Western Cape Province, South Africa. The sample included 1097 treatment episodes, representing 32% of all episodes in 2019. Using multivariate logistic regression, we modelled socio-demographic, substance use and treatment correlates of patient-reported suboptimal access to, quality and outcomes of SUD treatment. Results: Overall, 37.9% of patients reported substantial difficulties in accessing treatment, 28.8% reported suboptimal quality treatment, and 31.1% reported suboptimal SUD outcomes. The odds of reporting poor access were elevated for patients identifying as Black/African, in residential treatment, with comorbid mental health problems, and longer histories of substance use. Length of substance use, comorbid mental health problems, and prior SUD treatment were associated with greater likelihood of reporting suboptimal quality treatment. Patients with comorbid mental health problems, polysubstance use, who did not complete treatment, and who perceived treatment to be of poor quality were more likely to report suboptimal outcomes. Conclusion: This study is among the first to use patient-reported experiences and outcome measures to identify targets for SUD treatment improvement. Findings suggest substantial room to improve South African SUD treatment services, with targeted efforts needed to reduce disparities in outcomes for patients of Black/African descent, for those with comorbid mental health problems, and for patients who have chronic substance use difficulties. Interventions to enhance the relevance, appropriateness, and acceptability of SUD services for these patient sub-groups are needed to improve system performance.